2010
DOI: 10.1073/pnas.0911186107
|View full text |Cite
|
Sign up to set email alerts
|

PMCA2 regulates apoptosis during mammary gland involution and predicts outcome in breast cancer

Abstract: After lactation, weaning causes mammary epithelial cell (MEC) apoptosis. MECs express the plasma membrane calcium-ATPase 2 (PMCA2), which transports calcium across the apical surface of the cells into milk. Here we show that PMCA2 is down-regulated early in mammary involution associated with changes in MEC shape. We demonstrate that loss of PMCA2 expression raises intracellular calcium levels and sensitizes MECs to apoptosis. In contrast, overexpression of PMCA2 in T47D breast cancer cells lowers intracellular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
148
2
8

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 115 publications
(167 citation statements)
references
References 39 publications
9
148
2
8
Order By: Relevance
“…A recent study showed that elevated PMCA2 expression in mammary epithelial cells inhibited apoptosis and in human breast cancer cases a high PMCA2 mRNA level was associated with poor clinical prognosis [62]. In breast cancer cell lines PMCA1 and PMCA2 was shown to be expressed at an increased level compared to non-tumorigenic cells [11,12] although, in one study PMCA2 mRNA was not detected by RT-PCR in MCF-7 cells [63].…”
Section: Discussionmentioning
confidence: 97%
“…A recent study showed that elevated PMCA2 expression in mammary epithelial cells inhibited apoptosis and in human breast cancer cases a high PMCA2 mRNA level was associated with poor clinical prognosis [62]. In breast cancer cell lines PMCA1 and PMCA2 was shown to be expressed at an increased level compared to non-tumorigenic cells [11,12] although, in one study PMCA2 mRNA was not detected by RT-PCR in MCF-7 cells [63].…”
Section: Discussionmentioning
confidence: 97%
“…After weaning, PMCA2 expression rapidly decreases, contributing to the initiation of programmed cell death and mammary gland involution (7,8). PMCA2 is also expressed in breast cancers (8)(9)(10), and high levels of tumor PMCA2 expression predict increased mortality in patients (8).…”
mentioning
confidence: 99%
“…PMCA2 (gene symbol Atp2b2) is highly expressed in the apical membrane of mammary epithelial cells only during lactation, where it has been shown to transport calcium into milk (4-6). After weaning, PMCA2 expression rapidly decreases, contributing to the initiation of programmed cell death and mammary gland involution (7,8). PMCA2 is also expressed in breast cancers (8-10), and high levels of tumor PMCA2 expression predict increased mortality in patients (8).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The remaining three, which are members of the Casein gene family, are also major proteins during lactation. As for the 7-fold down-regulated gene, Atp2b2, whose structure is similar to those of the SERCA calcium pumps, this function as a calcium transporter that moves calcium across the apical surface of cells into the milk [48,49]. The Lpo gene encodes an oxidoreductase that acts as a natural antibacterial agent in the innate immune system by killing bacteria in milk.…”
Section: Decisive Changes In Both Hk and Ms Gene Regulation During Thmentioning
confidence: 99%